The Impact of Marketing Mix towards Customer Loyalty Mediated by Customer Satisfaction of Blackberry Indonesia - Raymond Sukamto; Daniel Lumintan (iBuss Management, 2015)
This research conducted to know the impact of Marketing Mix strategy toward customer loyalty mediated by customer satisfaction of Blackberry Indonesia. The data gathered using simple random sampling method and distribute questionnaires to 102 respondents who ever used or own Blackberry. The data then being analyzed by Path Analysis and Sobel Test The result shown that marketing mix simultaneously having significant impact toward customer loyalty mediated by customer satisfaction of Blackberry Indonesia. However, only one of marketing mix element which is product is not significant toward customer loyalty of Blackberry Indonesia.  Keywords: Customer loyalty, Customer Satisfaction, Marketing Mix.